Determinants for utilization and transitions of long-term care in adults 65+ in Germany: results from the longitudinal KORA-Age study - Steinbeisser, Kathrin (BMC Geriatr, 2018)
BACKGROUND: Societies around the world face the burden of an aging population with a high prevalence of chronic conditions. Thus, the demand for different types of long-term care will increase and change over time. The purpose of this exploratory study was to identify determinants for utilization and transitions of long-term care in adults older than 65 years by using Andersen’s Behavioral Model of Health Services Use. METHODS: The study examined individuals older than 65 years between 2011/2012 (t(1)) and 2016 (t(2)) from the population-based Cooperative Health Research in the Region of Augsburg (KORA)-Age study from Southern Germany. Analyzed determinants consisted of predisposing (age, sex, education), enabling (living arrangement, income) and need (multimorbidity, disability) factors. Generalized estimating equation logistic models were used to identify determinants for utilization and types of long-term care. A logistic regression model examined determinants for transitions to long-term care over four years through a longitudinal analysis. RESULTS: We analyzed 810 individuals with a mean age of 78.4 years and 24.4% receiving long-term care at t(1). The predisposing factors higher age and female sex, as well as the need factors higher multimorbidity and higher disability score, were determinants for both utilization and transitions of long-term care. Living alone, higher income and a higher disability score had a significant influence on the utilization of formal versus informal long-term care. CONCLUSION: Our results emphasize that both utilization and transitions of long-term care are influenced by a complex construct of predisposing, enabling and need factors. This knowledge is important to identify at-risk populations and helps policy-makers to anticipate future needs for long-term care. TRIAL REGISTRATION: Not applicable ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12877-018-0860-x) contains supplementary material, which is available to authorized users.